Impact of accentuated cut edges, yeast strain, and malolactic fermentation on chemical and sensory profiles of Sauvignon blanc wine. (30th January 2023) - Wang, Xingchen; Capone, Dimitra L.; Roland, Aurélie; Jeffery, David W.
Graphical abstract: Highlights: Accentuated cut edges (ACE) technique was applied to Sauvignon blanc winemaking. ACE improved varietal thiol and precursor concentrations over traditional crushing. Interactions with yeast and lactic acid bacteria affected thiol enantiomers. Treatment interactions impacted esters, higher alcohols, fatty acids, isoprenoids. ACE had less impact on wine sensory profile than yeast and lactic acid bacteria. Abstract: This pioneering investigation involved the application of accentuated cut edges (ACE) technique to Sauvignon blanc winemaking. The concentration of varietal thiol precursors in juice was significantly higher for ACE treatment compared to conventional crushing, with two-way or three-way interactions of the experimental factors, which included yeast strain and malolactic fermentation, being determined from the wine data. ACE yielded higher concentrations of 4-methyl-4-sulfanylpentan-2-one (4-MSP) and enantiomers of 3-sulfanylhexanol (3-SH) and 3-sulfanylhexyl acetate (3-SHA) in wines that were more abundant in phenolic compounds. Compared to Sauvy yeast strain, VIN13 produced greater amounts of 3-SH and 3-SHA but less 4-MSP with wines exhibiting lower intensity 'floral' and 'fruity' notes. MLF increased 3-SH and 4-MSP concentrations and led to wines that exhibited more non-fruity sensory attributes. The study revealed the potential of ACE for increasing varietal thiol concentrations in Sauvignon blanc wine and altering overall sensory profiles, with interactions involving yeast strain and MLF.